From skincare to watercare: Tackling salicylic acid pollution with hybrid glow plasma-cavitation technology - Federico Verdini; Nicolò Desogus; Emanuela Calcio Gaudino; Giancarlo Cravotto (Ultrasonics Sonochemistry, 2025)
Salicylic acid (SA), widely used in dermatological pharmaceuticals and as a primary metabolite of aspirin, is frequently detected in wastewater treatment plants (WWTPs) at concentrations between 3 and 900 mg/L. Given the ECHA’s predicted no-effect concentration (PNEC) of 162 mg/L for sewage treatment plants (STPs), high SA levels pose a risk to microbial communities responsible for biological oxidation. This study explores an innovative hybrid advanced oxidation process (AOP) that combines hydrodynamic cavitation (HC) and electrical discharge (ED) plasma for SA degradation, targeting environmentally friendly pretreatment before secondary biological treatment. Experiments were conducted at the pilot scale (5 L volume, 330 L/h flow rate) using model solutions with SA concentrations of 40 and 80 mg/L. While SA is typically used as a chemical dosimeter for hydroxyl radical (•OH) quantification in cavitational processes, its rapid degradation under HC/ED plasma prevents such use in this setup. For comparison, lab-scale ultrasound (US)-assisted treatments (500 kHz, 250 W, 0.1 L) were performed as a benchmark. HC/ED plasma treatment achieved over 98 % SA removal in both deionized and tap water within 20 min, whereas US treatment achieved only 54 % and 37 % removal after 120 min. Energy yield and electrical energy per order (EEO) analyses revealed that HC/ED is significantly more energy-efficient than US, particularly in tap water. Finally, the HC/ED method was evaluated through a Technology Readiness Level (TRL) assessment to estimate its scalability and applicability in real WWTP scenarios.